2020
DOI: 10.1128/msphere.00371-20
|View full text |Cite
|
Sign up to set email alerts
|

Candida auris Phenotypic Heterogeneity Determines Pathogenicity In Vitro

Abstract: Candida auris is an enigmatic yeast that provides substantial global risk in health care facilities and intensive care units. A unique phenotype exhibited by certain isolates of C. auris is their ability to form small clusters of cells known as aggregates, which have been to a limited extent described in the context of pathogenic traits. In this study, we screened several nonaggregative and aggregative C. auris isolates for biofilm formation, where we observed a level of heterogeneity among the different pheno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 70 publications
(112 reference statements)
4
52
0
2
Order By: Relevance
“…Although C. auris biofilms are thinner than those of C. albicans [ 46 ], the capacity of C. auris to form a biofilm has been clearly associated with a lower antifungal susceptibility [ 16 , 47 ]. The ability of C. auris to form a biofilm has been reported for both aggregating and non-aggregating phenotypes [ 12 ]. Biomass values obtained in the current study were similar to those reported by Sherry et al (2017) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although C. auris biofilms are thinner than those of C. albicans [ 46 ], the capacity of C. auris to form a biofilm has been clearly associated with a lower antifungal susceptibility [ 16 , 47 ]. The ability of C. auris to form a biofilm has been reported for both aggregating and non-aggregating phenotypes [ 12 ]. Biomass values obtained in the current study were similar to those reported by Sherry et al (2017) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, these authors reported the highest biofilm-forming capacity for non-aggregating isolates. Brown and coworkers [ 12 ] also detailed differences in gene expression between both phenotypes: genes related to cellular components (membrane and cell wall constituents) were upregulated in isolates with aggregating phenotype whereas genes related to biological processes and metabolic functions were expressed higher in non-aggregating isolates. Moreover, Short et al (2019) [ 48 ] suggested that the ability of C. auris to form cellular aggregates increases survival of the yeast, which coincided with the upregulation of biofilm-associated genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations